PENDAMPINGAN PEMBUDIDAYAAN SAYURAN DENGAN SISTEM HIDROPONIK MENGGUNAKAN MEDIA HASIL PENGOLAHAN SAMPAH ORGANIK - Andik Lukito Suryaman; Imam Mukhtar Syarifudin; Isna Laila; Sugianto Sugianto; Susi Darmawaningsih; Wiwit Wiji Lestari; Rachmadania Akbarita (Politeknik Negeri Sriwijaya, 2021)
The cultivation of vegetables with a hydroponic system is one of the ways that vegetable farming has no need for space and is easy for plant treatment.Deep flow Technique (DFT) is a method found in hydroponics with an excess of one is that although there are no water in installations, plants still receive nourishment from the stagnant water in the instalation.For the media used on the cultivation of the team and the Karang Taruna Kemloko 8 are the products of organic waste treatment taken from the scattered leaves in the enviroment.With an abundance of media and content (organic waste treatment and nutrients from running water) can produce good vegetables and can have high selling value.From the harvest of these organic vegetables people will be able to improve the economy well, for in this process people know ways that the cultivation of organic plants requires large tracts of land and complex treatments.